2015
DOI: 10.1152/jn.00745.2014
|View full text |Cite
|
Sign up to set email alerts
|

Postactivation depression of the Ia EPSP in motoneurons is reduced in both the G127X SOD1 model of amyotrophic lateral sclerosis and in aged mice

Abstract: Postactivation depression (PActD) of Ia afferent excitatory postsynaptic potentials (EPSPs) in spinal motoneurons results in a long-lasting depression of the stretch reflex. This phenomenon (PActD) is of clinical interest as it has been shown to be reduced in a number of spastic disorders. Using in vivo intracellular recordings of Ia EPSPs in adult mice, we demonstrate that PActD in adult (100-220 days old) C57BL/6J mice is both qualitatively and quantitatively similar to that which has been observed in larger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 109 publications
2
14
0
Order By: Relevance
“…Muscle stretch usually results in high frequency trains of action potentials in Ia afferents causing Excitatory Post Synaptic Potentials (EPSPs) in spinal motoneurones which are normally reduced in amplitude at these high frequencies due to post activation depression. We have previously shown that post activation depression of the Ia EPSP is reduced in the G127X mouse at a similar presymptomatic age to the current study 39 . Such a reduction in depression equates to a subtle increase in the amplitude of Ia EPSPs which may compensate for reduction in the sensitivity of the muscle spindles potentially due to reduced gamma motoneurone excitability.…”
Section: Discussionsupporting
confidence: 85%
“…Muscle stretch usually results in high frequency trains of action potentials in Ia afferents causing Excitatory Post Synaptic Potentials (EPSPs) in spinal motoneurones which are normally reduced in amplitude at these high frequencies due to post activation depression. We have previously shown that post activation depression of the Ia EPSP is reduced in the G127X mouse at a similar presymptomatic age to the current study 39 . Such a reduction in depression equates to a subtle increase in the amplitude of Ia EPSPs which may compensate for reduction in the sensitivity of the muscle spindles potentially due to reduced gamma motoneurone excitability.…”
Section: Discussionsupporting
confidence: 85%
“…; Hedegaard et al . ). It is hypothesized that the mechanisms that underlie post‐activation depression involve a decrease in the probability that neurotransmitter quantal release from Ia afferent will occur as a result of its prior activation (Kuno, ,b; Hirst et al .…”
Section: Discussionmentioning
confidence: 97%
“…RDD involves an attenuation of H-reflex amplitude following repetitive stimulations (Lloyd & Wilson, 1957;Ishikawa et al 1966;Meinck, 1976) and it is reduced in spastic humans (Nielsen et al 1993;Aymard et al 2000) and animals (Lee et al 2014b;Hedegaard et al 2015). C, blocking degradation of NKCC1 prevents a-tsDCS induced reduction of spasticity.…”
Section: Discussionmentioning
confidence: 99%
“…; Pelletier & Cicchetti, ; Hedegaard et al . ). However, we used single conditioning stimuli rather than trains, because single stimuli resulted in a comparable post‐activation depression.…”
Section: Methodsmentioning
confidence: 97%
“…; Hedegaard et al . ). Abnormally strong presynaptic inhibition and post‐activation depression might, in contrast, contribute to the weakening of synaptic input to spinal motoneurons found in recent studies of spinal muscular atrophy by Mentis et al .…”
Section: Introductionmentioning
confidence: 97%